CHARACTERISTICS OF DOLOMITIZED LIMESTONE OF PRUPUH FORMATION BASED ON PETROGRAPHY ANALYSIS IN SENDANG AGUNG, EAST JAVA - Putra, Andri Perdana (Faculty of Geological Engineering, Universitas Padjadjaran, 2018)
The East Java Basin is a large hydrocarbon producing basin in Java. From the drilling wells in thisregion it is known that the reservoir comes from carbonate rocks. The Prupuh Formation acts as areservoir because of its high porosity value, not only primary porosity but also secondary porosity.The study of limestone characteristics of Prupuh Formation in Sendang Agung Village, PaciranDistrict, Lamongan Regency, East Java Province is a combination of field and laboratory activities.Field activities include collecting data through detailed measurements, making measuredstratigraphic cross sections with systematic rocks sampling. Laboratory activities are petrographicanalysis through thin sections. The purpose of this study is to increase the knowledge aboutPrupuh limestone which acts as a reservoir in the East Java Basin oil and gas system. Based on theresults of the field activity, a measured stratigraphic section with a thickness of 32.5 meters wasmade, the lower and middle sections were composed of dolomite, then at the top there werebioclastic limestones as reported by Pringgoprawiro, 1983. A total of 6 (six) rock samples werechosen for petrographic analysis of thin sections. Results of the analysis obtained 32 meters is acrystalline dolomite with a very bad porosity system. Dolomite which is found is the result ofdolomitization of the wackestone bioclastics limestone. So it was concluded that the carbonaterocks the Prupuh Formation in research area had very bad potential to become reservoir rocks.